2021
DOI: 10.1002/essoar.10503623.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Bayesian model for quantifying errors in citizen science data: application to rainfall observations from Nepal

Abstract: High-quality citizen science data can be instrumental in advancing science toward new discoveries and a deeper understanding of under-observed phenomena. However, the error structure of citizen scientist (CS) data must be well-defined. Within a citizen science program, the errors in submitted observations vary, and their occurrence may depend on CS-specific characteristics. This study develops a graphical Bayesian inference model of error types in CS data. The model assumes that (1) each CS observation is subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Similarly, Cumming & Henry (2019) corrected for observation effort to account for imperfect detection. More recently, Eisma et al (2020) suggested a measurement error model to adjust for biases and errors in reports of rainfall measurement data produced by volunteers in Nepal.…”
Section: Bayesian Methods For Citizen Sciencementioning
confidence: 99%
“…Similarly, Cumming & Henry (2019) corrected for observation effort to account for imperfect detection. More recently, Eisma et al (2020) suggested a measurement error model to adjust for biases and errors in reports of rainfall measurement data produced by volunteers in Nepal.…”
Section: Bayesian Methods For Citizen Sciencementioning
confidence: 99%